SCIENCE AND UNESCO MEETING AT MEXICO CITY - ANONIMO (ORGANIZACION PARA LA EDUCACION, LA CIENCIA Y LA CULTURA DE LAS NACIONES UNIDAS, CD. MEXICO, DF, MEX, 1951)
MEETING AT MEXICO CITY IN this article we are concerned mainly with the present results from the successful drive to put the 'S* into 'U.N.E.C.O.'. The presence of some thirty scientific men from the thirty-three countries represented at the second genera
NATURE
Keywords: SCIENCE, UNESCO, MEETING, MEXICO CITY; MULTIDISCIPLINARIA; FILOSOFIA DE LA CIENCIA; CIENCIAS HUMANAS